Effectiveness of pharmacological treatments for COVID-19 due to SARS-CoV-2: a systematic literature review - Garcia Vidal, Carolina; González, Jonathan; Lumbreras, Carlos; Salavert, Miguel; Castro, Antonio; Rubio-Rodríguez, Darío; Rubio-Terrés, Carlos (Frontiers in Pharmacology, 2025)
AimSince the first cases of the COVID-19 pandemic, caused by the SARS-CoV-2 virus, described in 2019, numerous drugs have been proposed for the treatment of the disease. However, studies have given contradictory or inconclusive results, making it difficult to determine which treatments are truly effective. The objective was to carry out a systematic review of the literature analyzing the effectiveness (mortality, hospitalization and clinical improvement) of COVID-19 treatments initially proposed and finally authorized in the European Union.MethodsPubMed and other electronic databases were systematically searched for meta-analyses published between January 2020 and December 2022, as well as two additional searches: one of individual clinical studies published until October 2023 and another of those drugs that were considered at the beginning and that were discarded early because the clinical results were unfavorable.ResultsIn the synthesis, 85 meta-analyses and 19 additional clinical studies were included (base case). All medications indicated in the treatment of COVID-19 have favorable efficacy results (mortality, hospitalization rate, clinical improvement) but these results were not confirmed in all studies carried out, being frequently contradictory (confirming or not confirming the impact of treatment on mortality). According to meta-analysis with the largest sample size, the drugs with the greatest evidence of effectiveness in reducing mortality are remdesivir (HR= 0.79; 95% CI 0.73–0.85) and tocilizumab (OR= 0.73; 95% CI 0.56–0.93). Regarding the composite of Covid-19–related hospitalization or death from any cause, the drugs with the greatest evidence of efficacy are remdesivir, nirmatrelvir/ritonavir and sotrovimab (although, currently the effectiveness of monoclonal antibodies against the new variants of the virus has not been demonstrated).ConclusionAccording to this systematic review, the treatments with the greatest evidence of reducing mortality in patients with COVID-19 are remdesivir and tocilizumab.